Answer:
[tex]x=c.a^{-1}.b^{-1}[/tex]
Step-by-step explanation:
Given equation,
[tex]axb = c-----(1)[/tex]
[tex](axb) ( a^{-1}.b^{-1} ) = c.(a^{-1}b{-1})[/tex]
[tex](xb)(a)(a^{-1}.b^{-1} ) = c.(a^{-1}b{-1})[/tex] ( commutative law of multiplication )
[tex](xb)(a.a^{-1}).b^{-1} = c.a^{-1}b{-1}[/tex] ( Associative property )
[tex](xb).e.b^{-1} = c.a^{-1}b{-1}[/tex]
[tex](xb).b^{-1}=c.a^{-1}.b^{-1}[/tex] ( identity property )
[tex]x.(b.b^{-1})=c.a^{-1}.b^{-1}[/tex] ( Associative property )
[tex]x.e=c.a^{-1}.b^{-1}[/tex]
[tex]x=c.a^{-1}.b^{-1}[/tex] ( identity property )